(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
The purpose of this paper is to describe -with basis in communication theories and semiotic studies- the intercultural relations that are generated by the protagonists of the Patricio Manns’s novel El corazón a contraluz: a rumano colonist and their young selk´nam captive; and by the protagonists of the Isabelle Autissier’s novel El amante de la Patagonia: a young servant coming from Scotland in love of a yámana fisher. Those relations, the linguistics in the first place, are favoured or obstructed by personal factors, as well as by influential factors of the historical context –from the end of the 19th century to the beginning of the 20th century–, distinguished by the conflict’s situation between the European colonists and native peoples of Tierra del Fuego.